2023
DOI: 10.1097/mbp.0000000000000612
|View full text |Cite
|
Sign up to set email alerts
|

Population attributable fraction estimates of cardiovascular diseases in different blood pressure levels in a large-scale cross-sectional study: a focus on prevention strategies and treatment coverage

Abstract: Objective Hypertension is one of the major modifiable risk factors in developing cardiovascular diseases (CVD). Hence, we aimed to ascertain age- and sex-specific population attributable fraction (PAF) for CVD in different blood pressure levels to implement efficient preventive strategies at the population level. Methods Participants’ data were obtained from the Iranian stepwise approach for surveillance of noncommunicable disease risk factors (STEPs) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…This necessitated the control of high SBP, FPG, BMI, and LDL to prevent a large proportion of death among adults in Iran (9,21). In addition, other studies in Iran found that high FPG, BMI, and total cholesterol were responsible for approximately onethird to one-half of high SBP-attributed deaths (3,22). Previous studies reported that 26.4% of adults were dealing with high SBP hypertension increased from 8.7 to 28.8% in women, and from 8.0 to 28.8% in men.…”
Section: Discussionmentioning
confidence: 99%
“…This necessitated the control of high SBP, FPG, BMI, and LDL to prevent a large proportion of death among adults in Iran (9,21). In addition, other studies in Iran found that high FPG, BMI, and total cholesterol were responsible for approximately onethird to one-half of high SBP-attributed deaths (3,22). Previous studies reported that 26.4% of adults were dealing with high SBP hypertension increased from 8.7 to 28.8% in women, and from 8.0 to 28.8% in men.…”
Section: Discussionmentioning
confidence: 99%